Photodegradation of Sulfadiazine in Aqueous Solution and the Affecting Factors - Xuesen Bian; Jibing Zhang (Journal of Chemistry)
Knowledge about photochemical behavior of sulfonamides under UV light is limited. In this study, photodegradation of sulfadiazine in water by ultraviolet (UV) light was studied using a 300 W, 365 nm UV lamp. The degradation process followed well the first-order kinetics, with a half-life of 9.76 min in water with air saturation. The photodegradation was slower at acidic pH 4.52 than at pH 6.98 and pH 8.90. Addition of H2O2 and nitrate enhanced the photodegradation rate, while addition of ethanol, nitrite, sulfate, and bicarbonate depressed the reaction rate. This study suggested that sulfadiazine photodegradation under UV light is generally favored by the attack of hydroxyl radicals.